DEVELOPING STUDENTS’ FACILITY IN COMMUNICATIVE INTERACTION TECHNIQUES OUTSIDE THE LANGUAGE LEARNING CLASSROOM AT NON-LINGUISTIC FACULTIES - Druzhinina, Rimma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article focuses on some new insights into the effects of students’ communicative interaction in the language learning process. The study offers some modes of utilizing the extra-curricular activities potential for generating an interaction environment where students venture into true communication. The syllabus of students’ interaction within their extra-curricular activities has been defined in the study in relation to the video conferencing technology. We have expanded the range of educational offerings while introducing some components of video conferencing into students’ communicative learning: virtual meeting rooms, discussion forums, screen sharing. The topicality of the study consists in insufficient number of scientific works on aspects of students’ communicative interaction within extra-curricular activities in language learning. Hence the aim of the study is to propose theoretical justification and methodological development of utilizing the interaction potential within extra-curricular activities for students’ communication training. Following the aim we have examined characteristics of students’ communicative interactions within extra-curricular cases in language learning. We have elaborated some techniques and devices, identified some ways of generating communicative interaction dynamics for furthering students’ communication training. We have verified the findings in our experimental practical work and have revealed the significance of students’ interactions within extra-curricular activities for facilitating their communication potential in language learning.